Interaction of vitamin D, homocystein and dental diseases - O. V. Kuriata; M. M. Hrechanyk (Zaporožskij Medicinskij Žurnal)
The aim of the study was to estimate the effect of ursodeoxycholic acid (UDCA) on the lipid profile, endothelial dysfunction and insulin resistance in patients with coronary heart disease (CHD) in combination with non-alcoholic steatosis.